QUO VADIS HAK POLITIK MANTAN NARAPIDANA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 42/PUU-XII/2015 - Widyatama, Alfian; Isharyanto, Isharyanto (Res Publica: Jurnal Hukum Kebijakan Publik, 2019)
This study aims to determine the political rights of ex-prisoners who wish to participate in the contestation of democratic parties in the context of elections after the Decision of the Constitutional Court Number 42 / PUU-XII / 2015.. The research method used is normative legal research. The approach used is the approach of law and case approach. Sources of legal materials used are primary and secondary legal materials. The Constitutional Court through Decision Number 42 / PUU-XIII / 2015 states that the form of reduction in the right to honor which can be equated with the criminal revocation of certain rights with the condition that someone has been sentenced to prison for committing a crime is threatened with imprisonment of five years or more . Restrictions on the political rights of ex-prisoners to participate in electoral contestations are in line with the demands of the need for someone who wants to fill public positions that are truly clean without legal defects that are identical to the damage to moral values, religion, public order in a person. the former prisoner.